ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA DI KOTA JAMBI - DEVITA ANDRI; IRMANELLY IRMANELLY (Develop: Jurnal Ekonomi Pembangunan, 2021)
This study is entitled "Analysis of Factors Affecting Labor in the City of Jambi". The purpose of this study is the first to determine and analyze the absorption of labor in Jambi City. Second, to analyze the influence of the factors that influence the absorption of labor in Jambi City. The research method used is secondary data analysis with the aim of the research is descriptive analysis method to answer the first objective used to identify how much increase in the workforce in Jambi City from time to time in a series of data during the period 2007 to 2018. Both tools The analysis used is multiple linear regression using the SPSS series 22 application. The results of the analysis carried out concluded, firstly, the development of labor absorption in Jambi City also experienced fluctuating increases during the 2007-2018 period. Second, partially based on the t test and F test of the independent variable of economic growth (X1), investment (X2) and the provincial minimum wage (X3) have a positive and significant effect on labor absorption (Y) in Jambi City during the 2007- 2018 period.